ACADEMIC COLONIALISM. HOLOCAUST STUDIES IN POLAND - Wolski, Paweł (Porównania, 2013)
The study of the Holocaust literature in Poland goes a long way back but as a separate discipline it has existed for a very short time. This is mostly due to the fact that until recently it had been part of other fields of study, including, mostly, war literature. A specific feature of this process is that the transformation from literary studies dealing with the Holocaust as one of the themes of proper Holocaust (literary) studies in Poland has been developing under strong influence of foreign – mainly American – Holocaust studies as an already evolved discipline. Therefore, Polish Holocaust studies have practically assumed the shape it has already had, but under a different name. In the paper I call this process academic (auto)colonialism and make an attempt to indicate its core features.